Upregulation of P2Y2R, Active uPA, and PAI-1 Are Essential Components of Hantavirus Cardiopulmonary Syndrome - Bondu, Virginie; Bitting, Casey; Poland, Valerie L.; Hanson, Joshua A.; Harkins, Michelle S.; Lathrop, Sarah; Nolte, Kurt B.; Lawrence, Daniel A.; Buranda, Tione (Frontiers in Cellular and Infection Microbiology, 2018)
Sin Nombre virus (SNV) causes hantavirus cardiopulmonary pulmonary syndrome (HCPS) with the loss of pulmonary vascular endothelial integrity, pulmonary edema without causing cytopathic effects on the vascular endothelium. HCPS is associated primarily with a dysregulated immune response. We previously found occult signs of hemostatic imbalance in the form of a sharp >30-100 fold increase in the expression of plasminogen activator inhibitor type 1 (PAI-1), in serial blood plasma draws of terminal stage-patients. However, the mechanism of the increase in PAI-1 remains unclear. PAI-1 is a primary inhibitor of fibrinolysis caused by tissue plasminogen activator (tPA) and urokinase plasminogen activator plasma (uPA). Here, we investigate factors that contribute to PAI-1 upregulation during HCPS. Using zymography, we found evidence of PAI-1-refractory uPA activity and no tPA activity in plasma samples drawn from HCPS patients. The sole prevalence of uPA activity suggested that severe inflammation drove PAI-1 activity. We have recently reported that the P2Y2 receptor (P2Y2R) mediates SNV infectivity by interacting in cis with 3 integrins, which activates the latter during infection. P2Y2R is a known effector for several biological processes relevant to HCPS pathogenesis, such as upregulation of tissue factor (TF), a primary initiator of the coagulation cascade, stimulating vascular permeability and leukocyte homing to sites of infection. As P2Y2R is prone to upregulation under conditions of inflammation, we compared the expression level of P2Y2R in formalin fixed tissues of HCPS decedents using a TaqMan assay and immunohistochemistry. Our TaqMan results show that the expression of P2Y2R is upregulated significantly in HCPS cases compared to non- HCPS controls (P< 0.001). Immunohistochemistry showed that lung macrophages were the primary reservoir of high and coincident localization of P2Y2R, uPA, PAI-1, and TF antigens. We also observed increased staining for SNV antigens in the same tissue segments where P2Y2R expression was upregulated. Conversely, sections of low P2Y2R expression showed weak manifestations of macrophages, SNV, PAI-1, and TF. Coincident localization of P2Y2R and PAI-1 on macrophage deposits suggests an inflammation-dependent mechanism of increasing pro-coagulant activity in HCPS in the absence of tissue injury.